2007
DOI: 10.1002/hep.21475
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protection by the JNK inhibitor leflunomide rescues mice from acetaminophen-induced liver injury

Abstract: Acetaminophen (APAP) is a widely used analgesic and antipyretic drug that is safe at therapeutic doses but which can precipitate liver injury at high doses. We have previously found that the antirheumatic drug leflunomide is a potent inhibitor of APAP toxicity in cultured human hepatocytes, protecting them from mitochondria-mediated cell death by inhibiting the mitochondrial permeability transition. The purpose of this study was to explore whether leflunomide protects against APAP hepatotoxicity in vivo and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
123
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 44 publications
7
123
3
1
Order By: Relevance
“…The role of JNKs in AILI has also been studied in WT mice in vivo with the use of pharmacological inhibitors [14,21,22,35] and anti-sense oligonucleotides [21 ]. Treatment of mice with pharmacological inhibitors that blocked the activity of both JNK1 and 2 reduced AILI and mortality, while administration of JNK2 but not JNK1 anti-sense oligonucleotides partially inhibited AILI when administered individually.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of JNKs in AILI has also been studied in WT mice in vivo with the use of pharmacological inhibitors [14,21,22,35] and anti-sense oligonucleotides [21 ]. Treatment of mice with pharmacological inhibitors that blocked the activity of both JNK1 and 2 reduced AILI and mortality, while administration of JNK2 but not JNK1 anti-sense oligonucleotides partially inhibited AILI when administered individually.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of mice with pharmacological inhibitors that blocked the activity of both JNK1 and 2 reduced AILI and mortality, while administration of JNK2 but not JNK1 anti-sense oligonucleotides partially inhibited AILI when administered individually. It was proposed that JNK had a pathological role in AILI in part by contributing to mitochondrial injury [14,21,35]. Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…JNK activation, particularly in the mitochondria, has been shown to exacerbate APAP-induced liver injury (24,25,27,47).…”
Section: Jnk Activation Was Differentially Regulated In Parkin Ko Andmentioning
confidence: 99%